Seaweed (Gracilariopsis funicularis) biochar incorporation into a goat manure–food waste vermicompost for optimized vermidegradation and nutrient release - Katakula, Asteria Aili Ndiipohamba; Gawanab, Werner; Handura, Bethold; Itanna, Fisseha; Mupambwa, Hupenyu Allan (Frontiers in Sustainable Food Systems, 2022)
Vermicomposts are organic fertilizer sources that are being promoted, however their concentration of macro nutrients such as (NPK) are very low. This study therefore evaluated the effects of amending goat manure – food waste mixture with biochar prepared from seaweed (Gracilariopsis funicularis) at 0% (control); 2%; 4%; 6% and 8% on vermicompost degradation and macro-nutrient release. After 10 weeks of vermicomposting the highest pH of 9.06 was observed within the control whilst the lowest was 8.7 in the 8% treatment. The electrical conductivity showed a positive relationship with the level of biochar incorporation with the highest of 16.5 mS/cm from the 8% treatment whilst the lowest was within the control with 6 mS/cm. There were no significant differences between treatments on humification parameters, however there were significant differences on the changes of C/N ratio with the final C/N ratio of 14.4; 14.9; 16.7; 15.1 and 14.4 for the control; 2%; 4%; 6%; and 8% treatments respectively. Higher incorporation rate resulted in the higher concentration of potassium with a value of 32.3 g/kg at week 8. The final percentage change in Olsen P was 19%: 14.2%; 7.3%; 4.1% and 3.0% for the 8%; 6%; control; 4%; and 2% treatments, respectively. An optimized level of 6 to 8 % biochar incorporation ratio can be recommended. However, incorporation of G. funicularis biochar does not seem to influence changes in the vermidegradation efficiency, though it can significantly improve the macro nutrients like P, K and Mg concentrations as well as the macro element concentrations.